Principles of web design - Sklar, Joel (Australia Cengage Learning, 2009)
Guides your students through the entire Web site creation process, while developing and enhancing your HTML, CSS, and visual design skills along the way. This title features sections on HTML5, CSS3, CSS page layouts, and enhanced navigation as well as technical updates and screen shots throughout.
COECS